JUSTIFICATION OF CONTAINER USING IN THE DESIGN OF CARGO DELIVERY SYSTEM (Transport systems and technologies, 2018)
Today, one of the widely used services provided by many freight forwarding companies (FFCs) is the LCL (Less than Container Load) delivery of cargo. There are no doubts about certain advantages of FCL (Full Container Load) delivery. Therefore, the duty of the freight forwarder is to inform the client of all positive and negative aspects of a particular type of container used, despite the size of cargo party. Along with this, modern forwarding companies do not have a methodical support that allows freight forwarders to promptly substantiate relevant decisions regarding the expediency of LCL or FCL delivery. In this regard, the purpose of the research is to develop a technology justifying the use of the container in the projecting of the delivery system. To achieve the goal, in the work were set and gradually solved certain tasks. In the process of solving the first problem, the positive and negative sides of LCL and FCL deliveries of goods are reflected. As a result of the solution of the second task, a procedure has been established for substantiating the tariff unit (weight or volume of the lot) for quotation of the rate of freight forwarder services for the delivery of cargo in the consolidated container. As a result of the third task solution, the technology of justifying the LCL delivery of cargo compared to its FCL delivery was developed.
Keywords: LCL delivery, FCL delivery, container, freight forwarding company, freight forwarding service